“You do the task and I will present it” as a parody of out-class collaboration among EFL Indonesian students - Yudhi Arifani; Khoirul Anwar; Sri Suryanti; Ruruh Mindari (Universitas Muhammadiyah Semarang, 2022)
This conceptual article addresses the crucial issue of out-class collaborative learning as understood and practiced among most EFL Indonesian students. With the popularity of collaborative learning among EFL students, collaborative learning in secondary as well as tertiary education has been largely influenced by group competition and product-based assessment. As a result, the dishonesty of collaborative learning occurs because of the absence of process-based approaches during out-class collaboration. This article elaborates the cause and practices of “You do the task and I will present it” as a form of collaborative learning. This article highlights the causes and effects of the deceitful collaborative learning process as well as proposes valuable recommendations for proper collaborative learning activities. Finally, the article proposed a collaborative learning model using a universal collaboration approach to overcome the deceitful practices of out-class collaborative learning.